101 sample write-ups for documenting employee performance problems : a guide to progressive discipline & termination - Falcone, Paul (AMACOM, 2017)
Managers may dread dealing with performance problems, but this sanity-saving guide by HR expert Paul Falcone is here to help. Revised to reflect the latest developments in employment law, the third edition of 101 Sample Write-Ups for Documenting Employee Performance Problems explains the disciplinary process and provides ready-to-use documents that eliminate the stress and second-guessing about what to do and say.
Revised edition of the author's 101 sample write-ups for documenting employee performance problems, c2010.
Keywords: Employees -- Dismissal of.; Labor discipline.; Problem employees.; elektronické knihy; electronic books